GISS Model E2.2: A Climate Model Optimized for the Middle Atmosphere—Model Structure, Climatology, Variability, and Climate Sensitivity. Issue 10 (23rd May 2020) - Rind, D.; Orbe, C.; Jonas, J.; Nazarenko, L.; Zhou, T.; Kelley, M.; Lacis, A.; Shindell, D.; Faluvegi, G.; Romanou, A.; Russell, G.; Tausnev, N.; et al.
Abstract: We introduce a new climate model (GISS E2.2) that has been specially optimized for the middle atmosphere and whose output is being contributed to the CMIP6 archive. The top of the model is at a geopotential altitude of 89 km, and parameterizations of moist convection and various forms of gravity wave drag based on tropospheric processes are chosen specifically for this optimization. We first evaluate the model in its configuration as a coupled atmosphere‐chemistry model with respect to its simulation of the mean state of the middle atmosphere, from the mesosphere down through the upper troposphere/lower stratosphere. Then we assess its use as a coupled atmosphere‐ocean climate model by exploring its mean ocean climatology. To evaluate its variability, we report on its simulation of the primary modes in the troposphere, stratosphere, and ocean. Two climate change simulations are presented, the responses to instantaneous increases of 2xCO2 and 4xCO2, run with two different ocean models. Sensitivity studies are performed to illustrate the effect of parameterizations on the model results. We compare these results to the lower vertical resolution/top GISS Model E2.1, whose output has also been submitted to CMIP6. The different choices made for these models are explored. It is shown that important improvements in the circulation above and below the tropopause can be obtained when attention is paid to representation of middle atmosphere processes in climate model development. Plain Language Summary: A new "high‐top" GISS climate model with results submitted to the CMIP6 archive is described, and the model development is explained. The model was optimized to produce a realistic middle atmosphere, which involved its simultaneous assessment along with its simulation of tropospheric climate. In particular, the interplay between the parameterization of convection in the troposphere and the dynamics of the middle atmosphere requires appreciation of the needs of both regions. Key Points: This article presents the new GISS "high‐top" climate model It discusses the advantages of a higher model top and increased vertical resolution It emphasizes the need for the middle atmosphere to be a focus in climate model development